(untitled) (World Bulletin of Management and Law, 2023)
The purpose behind using Mobile banking (M-banking) may be described as one of the services offered by a bank or other financial organization that enables its clients to do a range of banking activities using a mobile device, like a tablet, personal digital assistant or smart phone .